2021
DOI: 10.1002/term.3220
|View full text |Cite
|
Sign up to set email alerts
|

Airway ciliated cells regenerated on collagen sponge implants acquire planar polarities towards nearby edges of implanted areas

Abstract: Summary Tissue‐engineered tracheae have been developed to replace defective tracheae. However, the direction of ciliated cells in the regenerated epithelium remains unclear. We investigated planar polarity formed in the regenerated airway epithelium after tracheal graft implantation. We partially resected the rat trachea and implanted a collagen scaffold. The direction of the basal foot was assessed by transmission electron microscopy. Immunofluorescence staining was performed to examine the biased distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(59 reference statements)
0
0
0
Order By: Relevance
“…Regarding the importance of the direction of ciliary movement, Thomas et al [13] reported that epithelial ultrastructural abnormalities may increase the risk of allograft colonization by pathogenic organisms despite a normal CBF, suggesting that not only the CBF but also the direction of ciliary movement (such as the CTF, which is the calculated speed of oral directional transport along the lung-oral axis) may be more important for preventing infection. Although there is currently no method to unify the movement of cilia, the regulation of planar cell polarity might be essential to unify the direction of the airway epithelial cilia [7,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the importance of the direction of ciliary movement, Thomas et al [13] reported that epithelial ultrastructural abnormalities may increase the risk of allograft colonization by pathogenic organisms despite a normal CBF, suggesting that not only the CBF but also the direction of ciliary movement (such as the CTF, which is the calculated speed of oral directional transport along the lung-oral axis) may be more important for preventing infection. Although there is currently no method to unify the movement of cilia, the regulation of planar cell polarity might be essential to unify the direction of the airway epithelial cilia [7,14,15].…”
Section: Discussionmentioning
confidence: 99%
“…We then examined the long-term survival after implantation of the novel PGA material and the morphological characteristics and functional performance of the novel PGA material. According to our previous studies, the sample size was set at 5 rats per observational period: 2 weeks, 1 month, 2 months and 6 months after implantation [7]. However, because 2 rats were needed for the morphological and functional evaluation, the total sample size was set at 40 rats.…”
Section: Methodsmentioning
confidence: 99%